Efficacy and Safety of Lithium Treatment in SARS-CoV-2 Infected Patients - Spuch, Carlos; López-García, Marta; Rivera-Baltanás, Tania; Cabrera-Alvargonzález, J. J; Gadh, Sudhir; Rodrigues-Amorim, Daniela; Álvarez-Estévez, Tania; Mora, Almudena; Iglesias-Martínez-Almeida, Marta; Freiría-Martínez, Luis; Pérez-Rodríguez, Maite; Pérez-González, Alexandre; et al. (Frontiers in Pharmacology, 2022)
At the beginning of the pandemic, we observed that lithium carbonate had a positive effect on the recovery of severely ill patients with COVID-19. Lithium is able to inhibit the replication of several types of viruses, some of which are similar to the SARS-CoV-2 virus, increase the immune response and reduce inflammation by preventing or reducing the cytokine storm. Previously, we published an article with data from 6 patients with severe COVID-19 infection, where we proposed that lithium carbonate could be used as a potential treatment for COVID-19. Now, we set out to conduct a randomized clinical trial number EudraCT 2020-002008-37 to evaluate the efficacy and safety of lithium treatment in patients infected with severe SARS-CoV 2. We showed that lithium was able to reduce the number of days of hospital and ICU admission as well as the risk of death, reduces inflammatory cytokine levels by preventing cytokine storms, and also reduced the long COVID syndromes. We propose that lithium carbonate can be used to reduce the severity of COVID-19.